Engine combustion : pressure measurement and analysis - Rogers, David (SAE International, 2021)
Engine Combustion: Pressure Measurement and Analysis, 2E provides practical information on measuring, analyzing, and qualifying combustion data, as well as details on hardware and software requirements and system components. Describing the principles of a successful combustion measurement process, the book will enable technicians and engineers to efficiently generate the required data to complete their development tasks. The revised edition has been updated with color photos and a fresh modern format has been adapted enhancing the readability of the book. As with the original printing, Engine Combustion: Pressure Measurement and Analysis, 2E is a comprehensive handbook for technicians and engineers involved in engine testing and development, and a valuable reference for scientists and students who wish to understand combustion measurement processes and techniques.
Keywords: Automobiles -- Motors -- Cylinders.; Automobiles -- Motors -- Combustion.; Pressure -- Measurement.; elektronické knihy; electronic books